Global Justice and the Priority of Basic Goods to Basic Freedoms: Reflexions on Amartya Sen’s Development and Freedom - Solís Umaña, Mario (Revista de Filosofía, 2012)
The paper examines Amartya Sen’s seminal work Development and Freedom (1999) in relation to his underlying conception of justice and particularly in relation to the tension that arises in the correlation between basic freedom and basic goods. The idea is to address the question as to which of the two elements (basic goods or basic freedoms) takes precedence to the enactment of global justice. The paper advances a particular distinction between a foundational approach and a functional approach when addressing the question of the priority and primacy of any of the two elements and sheds light on a contentious answer, namely, that basic goods are foundationally primary in relation to basic freedoms and that such a primacy does not rule out the functional priority of basic freedoms.